(untitled) (Revista Crioula, 2022)
Departing from the critical fortune on the writer Cassandra Rios, I analyze, based on the queer phenomenology by Sara Ahmed (2006) and Heather Love’s criticism on the genealogies of LGBTQIA+ history (2007), possibilities of re-elaborating past perceptions, as well as the literary and personal past of lesbian writer Cassandra Rios. The aim is to face the lacks and problematic elements present in the author's novels, often left aside by Cassandrian studies, in order to focus on the failures and queer negativity present in Cassandra Rios' writing. With this, it is hoped to pave the way for thinking about new possibilities and clues regarding a key element of Brazilian lesbian and LGBTQIA+ history.